2018
DOI: 10.1002/aenm.201803260
|View full text |Cite|
|
Sign up to set email alerts
|

Defect‐Rich Soft Carbon Porous Nanosheets for Fast and High‐Capacity Sodium‐Ion Storage

Abstract: Soft carbon has attracted tremendous attention as an anode in rocking‐chair batteries owing to its exceptional properties including low‐cost, tunable interlayer distance, and favorable electronic conductivity. However, it fails to exhibit decent performance for sodium‐ion storage owing to difficulties in the formation of sodium intercalation compounds. Here, microporous soft carbon nanosheets are developed via a microwave induced exfoliation strategy from a conventional soft carbon compound obtained by pyrolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
141
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(147 citation statements)
references
References 52 publications
6
141
0
Order By: Relevance
“…In addition, the D‐band can be fitted to four bands (Table S3, Supporting Information) . For DT‐C, the fitted curves show a significant improvement of the D1 band, corresponding to the more exposed edges on the carbon layer due to the dual templates assisted synthesis method . The calculated I D1 / I G ratio of DT‐C is 1.16, which is higher than that of HT‐C (1.09) and NT‐C (0.98).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the D‐band can be fitted to four bands (Table S3, Supporting Information) . For DT‐C, the fitted curves show a significant improvement of the D1 band, corresponding to the more exposed edges on the carbon layer due to the dual templates assisted synthesis method . The calculated I D1 / I G ratio of DT‐C is 1.16, which is higher than that of HT‐C (1.09) and NT‐C (0.98).…”
Section: Resultsmentioning
confidence: 99%
“…The change of defect degree is owing to the generation of irregular lattice brought by the templates. In addition, the D‐band can be fitted to four bands (Table S3, Supporting Information) . For DT‐C, the fitted curves show a significant improvement of the D1 band, corresponding to the more exposed edges on the carbon layer due to the dual templates assisted synthesis method .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Mai and co‐workers prepared microporous soft carbon nanosheets by microwave induced exfoliation. Structural characterization results showed that the surface area increased after exfoliation with the volume of micropores increased by more than 100 times, and the favorable defects on the edge of graphene layer were significantly increased . Due to the synergism‐enhanced kinetics and additional sodium storage sites provided by the micropores and defects at the edges, this material has high rate capacity.…”
Section: Defective Electrode Materials For Rechargeable Batteriesmentioning
confidence: 99%
“…In addition, the use of aluminum, instead of copper, for the negative current collectors in SIBs, can significantly reduce the whole weight of batteries and as a result effectively increase the energy density of batteries. On the basis of these advantages, a variety of advanced cathodes and anodes with delicately designed morphology and compositions have been successfully developed for SIBs, many of which now have been proven to have huge potential for commercial application …”
Section: Introductionmentioning
confidence: 99%